Ekspresi Pengarang dalam Cerpen “Dia Dulu Bukan GAM”: Pendekatan Ekspresif Abrams terhadap Sastra Konflik Aceh - Ifutya Warnisa; Bagaskara Nur Rochmansyah; Septian Fatianda (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the author's expression during the Aceh conflict period as found in the short story “Dia Dulu Bukan GAM” by Fazil Abdullah. The approach used is an expressive approach based on Abrams' theory. The data source in this study is the short story “Dia Dulu Bukan GAM” by Fazil Abdullah. The data in this study includes phrases and sentences found in the narrative of the story as well as the behaviors/feelings of the characters as depicted by the author in the short story. Data collection was carried out using the semiotic reading method. The steps that can be taken in analyzing literary works using Abrams' expressive approach are (1) understanding and carefully reading the literary work and analyzing a number of the author's thoughts, perceptions, feelings, and experiences that are present directly or indirectly in the work, (2) presenting the author's thoughts, perceptions, feelings, and experiences and relating the data obtained to the author's biography, and finally (3) draw conclusions. The results of the analysis found that the author's expressions reflected in the work include feelings, idealism, experiences, and social situations occurring around the author